Azole Resistance in Aspergillus fumigatus: A Five-Year Follow Up Experience in a Tertiary Hospital With a Special Focus on Cystic Fibrosis - Guegan, Hélène; Prat, Emilie; Robert-Gangneux, Florence; Gangneux, Jean-Pierre (Frontiers in Cellular and Infection Microbiology, 2021)
Azole-resistant Aspergillus fumigatus (ARAf) has emerged worldwide during the last decades. Drug pressure after long term treatments of chronically infected patients and the propagation of environmental clones selected under the pressure of imidazoles fungicides used in agriculture and farming both account for this emergence. The objectives of this study were to determine the rate of azole resistance in Aspergillus fumigatus during a 5-year period, taking into account (i) differences between underlying diseases of the patients treated, (ii) cross-resistance between azoles, and (iii) focusing on the 5-year evolution of our center’s cystic fibrosis cohort. Overall, the rates of voriconazole (VRC)-resistant and itraconazole (ITC)-resistant A. fumigatus isolates were 4.1% (38/927) and 14.5% (95/656), respectively, corresponding to 21/426 (4.9%) and 44/308 (14.3%) patients, respectively. Regarding cross-resistance, among VRC-R isolates tested for ITC, nearly all were R (20/21;95%), compared to only 27% (20/74) of VRC-R among ITC-R isolates. The level of azole resistance remained somewhat stable over years but greatly varied according to the azole drug, patient origin, and clinical setting. Whereas azole resistance during invasive aspergillosis was very scarce, patients with cystic fibrosis were infected with multiple strains and presented the highest rate of resistance: 5% (27/539) isolates were VRC-R and 17.9% (78/436) were ITC-R. These results underline that the interpretation of the azole resistance level in Aspergilllus fumigatus in a routine setting may consider the huge variability depending on the azole drug, the clinical setting, the patient background and the type of infection.